Is Adjuvant Chemotherapy Worthwhile After Radical Resection for Single Lung Metastasis From Colorectal Cancer? A Multicentric Analysis Evaluating the Risk of Recurrence - Rapicetta, Cristian; Lococo, Filippo; Davini, Federico; Carleo, Francesco; Kauppi, Juha; Di Stefano, Teresa Severina; Ricciardi, Sara; Di Martino, Marco; Räsänen, Jari; Paci, Massimiliano; Melfi, Franca; Cardillo, Giuseppe (Frontiers in Oncology, 2019)
Background. Adjuvant chemotherapy after resection of colorectal cancer (CRC) lung metastases may reduce recurrences and improve survival. The choice of best candidates for adjuvant chemotherapy in this setting is controversial, especially when a single lung metastases is resected. The aim of this study is to evaluate the risk of recurrence after radical resection for single lung metastasis from colorectal cancer (CRC). Patients and methods. Demographic, clinical and pathological data were retrospectively collected for patients radically operated for single pulmonary metastasis from CRC in 4 centers. Survival was computed by Kaplan-Meyer methods. Chi-square, log-rank test and, for multivariate analysis, Cox-regression and binary logistic regression were used when indicated. Results. The sample consisted of 344 patients, mean age 65-yrs. Overall 5-yrs survival was 61.9% respectively. Recurrence occurred in 113 pts (32,8%). At univariate analysis, age>70 (p=0.046) and tumour size>2 cm (p=0.038) were predictive of worst survival, while synchronous lung metastasis (p=0.039), previous resection of extrathoracic metastasis (p=0.017), uptake at FDG-PET scan (p=0.006) and short (<12 months) disease-free interval (DFI) prior to lung metastasectomy (p=0.048) were risk factor for recurrence. At multivariate analysis, only high CEA (>4 ng/mL) was associated to worst survival (HR: 4.3, p=0.014), while prior abdominal surgery (HR: 3, p=0.033), PET positivity (HR: 2.7, p=0.041) and DFI > 12 months (HR: 0.14, p<0.001) confirmed to predict recurrence of disease. Conclusions. Surgical resection of solitary lung metastases from CRC is associated with prolonged survival. High value of CEA, PET positivity, previous extrathoracic resected metastasis and short (<12 months) DFI were found to be predictive of death or disease recurrence and might identify in this scenario patients at higher risk which could potential benefit of chemotherapy.